Paisaje cultural y patrimonio. Producción y transformación de las salineras de Maras, Cusco - Delgado Antezana, Sebastián (Pontificia Universidad Católica del Perú, 2024)
Where are the architecture and landscape compared to the mode of territorial occupation in the Tahuantinsuyo? The research analyzes the Maras salt mines based on its status as a cultural landscape.Being a case study with a historical development in which pre-inca, inca, colonial and republican occupations have overlapped, the importance of Maras is still valid given that it has maintained salt as a constitutive element. The review of the productive and constructive processes of ancestral techniques is proposed, as well as the current cultural manifestations, based on a territorial reading of the limitations and interventions to make salt a product that particularizes the human activity of settlement around the salt of Maras in Cusco.

¿Dónde quedan la arquitectura y el paisaje frente al modo de ocupación territorial en el Tahuantinsuyo? La investigación analiza las salineras de Maras, en el Cusco, a partir de su condición de paisaje cultural. Si bien es un caso de estudio en cuyo devenir histórico se han superpuesto ocupaciones preincaicas, incaicas, coloniales y republicanas, la importancia de Maras permanece vigente dado que ha mantenido la sal como elemento constitutivo. Se propone la revisión de los procesos productivos y constructivos de las técnicas ancestrales, así como de las manifestaciones culturales vigentes, a partir de una lectura territorial de los factores limitantes y las intervenciones para hacer de la sal un producto que particulariza la actividad humana de asentamiento en torno a la sal de Maras.
Cultural Landscape and Heritage: Production and Transformation of the Maras Salt Mines, Cusco
Keywords: Maras salt mines; Cultural landscape; Territory; Salineras de Maras; Paisaje cultural; Territorio; https://purl.org/pe-repo/ocde/ford#6.04.08